SLOVAK FOOD INDUSTRY AND ITS POSITION ON THE DOMESTIC AND FOREIGN MARKETS - Maroš VALACH (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The subject of this article's analysis is the position of the Slovak food industry on the domestic and foreign markets. The period under review was 2015-2019. The identification of the share of Slovak products in the retail network was carried out on the basis of two methodological approaches, which are based on statistically available data, one in financial and the other in kind terms. Research results show that the food industry in the Slovak Republic is thriving, with revenues exceeding costs in the long term. Labour productivity from added value, which is an important economic indicator of the industry's competitiveness, grows over time, which is caused by a decrease in the workforce. On the domestic market, it is a priority to resist the pressure of foreign imports and to increase the share of Slovak products in domestic retail network. The low competitiveness of Slovak food products is reflected in the massive import of substitutable food products that can be produced domestically.